Morphometry of Anterior Cruciate Ligament - Banu, Jahira; Sontakke , Yogesh Ashok; Tamgire, Dharmaraj (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2018)
Anterior cruciate ligament (ACL) is one of the ligament in the complex knee joint. ACL is connecting the two bony structures maintaining the knee joint stability in anteroposterior direction. Stability of the joint can be disturbed in case of injuries to the knee joint. Surgeries in replacing the ligament are the best option for treating knee ligament injury. Graft replacement needed an appropriate size. Different parameters such as ACL length, width, cross sectional area, insertional area are borne to be in mind for preparation and proceeding the ACL surgery. Various parameters on morphometry of ACL are reviewed in this article. Studies of morphometry from cadaver and living subjects are included in the review. This article may give an idea about the parametric measurement of ACL and will guide the surgeons for the treatment of ACL injuries.